Analysis of Perceptions of Milk Consumption and Customer Service in the City of Riobamba, Province of Chimborazo - O. Parada Gutiérrez; J. Vasco; C. Delgado (ESPOCH Congresses)
The customer has become a source of strategic information about the quality of products and services. For this reason, the objective of this research was to analyze the level of service and mental processes of clients in making decisions to consume milk in the province of Chimborazo. Non-probabilistic sampling was used and data were collected from 50 clients and 75 representatives of small- and medium-sized companies in the city of Riobamba which participated in the Production Exhibition, Macají, Riobamba 2019. An electroencephalogram was used to determine whether the purchasing decisions were made at the unconscious level by reading brain waves. Three brands of milk that are sold locally were used. The study revealed that there were representative differences in stimulating people to different perceptions (visual, olfactory, gustatory) that influence the appreciation and purchasing decisions of milk. Similarly, it was found that there are decisions that the consumer makes unconsciously based on memories and past experiences that influence their present behavior at the time of consumption. The study also revealed the need to improve the level of service.